O cemitério da Soledade e o consumo do patrimônio cultural - SOUZA, Afonso Maria de Ligório Souza (2019)
This research is devoted to developing a work in and on the Graveyard of Solitude, which aimed to collect data with the belenense society, whose interpretations of substantiated order to show elements that may contribute to the composition of proposals to the graveyard land-use policies, understood as institutionalized cultural heritage, and identify and understand what the relations between the public who use the graveyard space. In this sense, we sought to identify the logic that takes place in the recognition of an institutionalized cultural property and its potential consumption, while symbolic representation, in order to attract public; generate resources; and its relationship with the individual consumer of a culture characterized by symbols that pose be triggered as memory and identity elements. Therefore, we implemented, as a methodology for the development of research: exploratory observation; the application of a questionnaire in on-mode and via the web; consultation documents in IPHAN file; bibliographical study in works from different areas of knowledge with emphasis on museological theory, the cultural heritage and the concepts of consumption.